Seed, fertilizer, and agricultural extension in Ethiopia - Spielman, David J.; Mekonnen, Dawit Kelemework; Alemu, Dawit (University of Pennsylvania Press, 2012)
Over the past two decades, decisionmakers in Ethiopia have pursued a range of policies and investments to boost agricultural production and productivity, particularly with respect to the food staple crops that are critical to reducing poverty in the country. A central aim of this process has been to increase the availability of improved seed, chemical fertilizers, and extension services for small-scale, resource-poor farmers, particularly those cultivating food staple crops. Although there is some evidence to suggest that the process has led to improvements in both output and yields during this period, decisionmakers still recognize that there is extensive room for improvement. And given the persistent food security issues facing Ethiopia year to year, there is a sense of urgency underlying the need for improvement.